Conditional trust as a driver of public engagement in Korea’s national project of bio-big data - Kim, Jae Sun; Kim, Seohyun; Lee, Cheyeon; Jeong, Wonoh; No, Huiwon; Lim, Sungsoo; Jung, Yul; Lee, Ilhak; Yang, Kwangmo (Frontiers in Genetics, 2026)
IntroductionTrust is built on the belief that promises will be honored. In biodata research, public trust is established when researchers conduct studies as promised and utilize the research outcomes in accordance with the stated objectives. Participants, particularly those contributing sensitive data, often demand a detailed explanation regarding how their data will be utilized and governed, which forms the foundation of trust. The National Project of Bio-Big Data (NPBBD) was conceived upon this premise. Within this framework, participants recognize the necessity of biobanks, the state ensures trustworthy governance through institutional safeguards, and researchers uphold these commitments—thereby sustaining a cycle of trust. Although prior studies have examined public attitudes toward biobanks and general willingness to participate, less is known about their perspectives on consent models, governance structures, benefit-sharing mechanisms, and motivations for engagement. Persistently low participation rates highlight the need for systematic analysis of underlying barriers and strategies to strengthen public involvement. Considering the NPBBD’s goal of building a nationwide cohort of one million individuals, this study seeks to identify the motivating factors that can foster improved public participation. By assessing public awareness and participation drivers, we aim to delineate the conditions of trust from the participants’ perspectives and offer guidance for data-driven policies grounded in medical, ethical, legal, and social legitimacy.MethodsBetween August 22–30, 2024, a web- and mobile-based survey was conducted among 1,027 adults aged 19–64 years, residing across 17 provinces and metropolitan cities in Korea, selected via proportional allocation. The questionnaire, developed with reference to prior studies including ethical, legal, and social implications, comprised 19 items across six domains, and 16 sociodemographic questions.ResultsOverall, 15.1% of the respondents were aware of the NPBBD, and 35.1% had heard of it, as compared to 49.1% who recognized the term “biobank.” Willingness to participate varied by incentive: 60.9% expressed willingness to participate when personal benefits were offered, 29.9% were motivated by public interest, and 9.3% declined participation altogether. Among the non-participants, 18.9% agreed to participate when presented with a rare disease scenario. Anticipated benefits included early detection and prevention (mean score: 78.3), treatment for rare or incurable diseases (76.5), and advancement of research (75.4). Key concerns centered on data breach (77.0), third-party misuse (76.1), and unconsented data use (75.6). Participation drivers included contribution to science (74.6), support for future generations (72.5), and personal benefits (68.1), with access to professional consultation (78.6) emerging as the most influential factor. The most desired information was genetic risk prediction (62.8%). Respondents favored receiving updates on sanctions for misuse (82.0%), supervisors assigned to monitor data use (80.3%), and ongoing research use (75.0%), through text messages (41.0%) and email (36.1%). Regarding additional data, 39.6% were willing to share information about their health, lifestyle, and habits; 38.0% preferred to share health information only; and 13.2% were ready to give biospecimens only. While the majority of participants favored reinvesting profits into drug and treatment development, others preferred receiving benefits through partial coverage of treatment costs (64.1%). In terms of governance, most respondents preferred a shared model involving government, public, and private institutions (44.7%). Consent preferences leaned toward dynamic (57.8%) over broad consent (35.2%).DiscussionPublic perception of biodata collection reflected a mix of anticipated personal and public benefits, alongside concerns regarding data disclosure. Willingness to participate was influenced more by personal benefits (60.9%) than by public interest (29.9%). While personal incentives such as treatment cost coverage were valued, participation was also driven by a desire to contribute to research and support drug development, reflecting a blend of self-interest and altruistic motivation. Concerns centered on data leakage, with dynamic consent emerging as a key condition of trust, alongside public governance and the right to information. To secure public trust and increase participation in the NPBBD, tailored strategies must be used to balance personal and public benefits with transparent governance, information provision, and consent procedures.